High perceived discrimination and no family support increase risk of poor quality of life in gender dysphoria - Hasan, Surilena; Alviany, Yovita; Clarissa, Cerellia; Sudana, Sonia (Universa Medicina, 2017)
BackgroundFamily support and low discrimination perceptions are a factor in protecting against mental disorders and poor quality of life in male to female (MtF) gender dysphoric individuals. The aim of this study was to determine the role of family factors, peer support, self-esteem, perceived discrimination, depression, anxiety, and stress on the quality of life among MtF gender dysphoric individuals. MethodsA cross-sectional study was conducted involving 106 MtF gender dysphoric individuals of Sanggar Swara Jakarta. Respondents filled out questionnaires on demographics, WHOQL-BREF, perceived discrimination, Rosenberg self-esteem, family support, social support (SSQ6), family relations (FACES III), and depression anxiety stress scale (DASS). Simple and multivariate logistic regression tests were used to analyze the data.ResultsAmong the 106 MtF gender dysphoric individuals of Sanggar Swara Jakarta with an age range of 18-45 years, 78.3% had no family support, 64.1% no peer support, 62.3% high perception discrimination, 64.1% low self-esteem, 36% extreme family relations, 44.3% depression, 59.4% anxiety, 35.8% stress and 62.3% poor quality of life. Employment, perception of discrimination, self-esteem, family support, and anxiety were significantly associated with quality of life (p<0.05). Multiple logistic regression analysis showed that perceived discrimination (Odds Ratio=13.89; 95% CI: 5.89-11.99), and family support (Odds Ratio=29.11; 95% CI: 2.45-8.21) were significantly associated with quality of life. Conclusion High perceived discrimination and no family support increase the risk of poor quality of life in MtF gender dysphoric individuals. These findings suggest the need for prevention and intervention of stigmatization and discrimination that should have a special focus on families with MtF gender dysphoric individuals.